Two-photon exchange contribution to elastic electron–proton scattering: measurements at the VEPP-3 storage ring; Physica Scripta; Vol. 166 - Rachek I. A. Igor Anatoljevich; Arrington J.; Dmitriev V. F. Vladimir Fedorovich; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Gramolin A. F. Alexander Valeryevich; Holt R. J.; Kaminsky V. V. Vyacheslav Viktorovich; Lazarenko V. A. Vyacheslav Aleksandrovich; Mishnev S. I. Svyatoslav Igorevich; Muchnoy N. Yu. Nikolay Yurjevich; Neyfeld V. V. Valery Valentinovich; Nikolenko D. M. Dmitry Mitrofanovich; et al. (2015, 2015)
Title screen